DIDACTIC POSSIBILITIES OF TEACHING PHYSICS TO ACADEMIC LYCEUM STUDENTS BASED ON THE STEM APPROACH - Oysanam daughter of Sultonbek Parpiyeva (Journal Park Publishing, 2025)
This study analyzes the didactic possibilities of teaching physics to academic lyceum students based on the STEM approach. It highlights ways to develop students’ scientific thinking and competencies through integrated teaching, practical tasks, and problem-based situations.
Keywords: STEM approach, physics, academic lyceum, didactic possibilities, integrated teaching.